(untitled) (Revista Científica Interdisciplinaria Investigación y Saberes, 2024)
The purpose of this article is to inform employers and workers in general about the importance of documenting the management by processes for the benefit of occupational safety, which productive or service companies must have in order to have safe working environments. What is described in first order are the statistics of work accidents in a period of five years and the legal aspects and pertinent public organisms of control, with which the public and private companies manage their plan of prevention labor risks in our national territory and then it is to make known on the importance that has the use and application of the technical tools of control and analysis that make possible to evidence, to analyze and to improve the enterprise processes. Finally, having managed to balance the process management, making it possible for workers to adopt a culture of doing things right from the first moment and thus improve labor productivity, reducing or eliminating hazards and risks associated with work and that lead to occupational accidents, with a good control at the source and in the middle, it will reduce or eliminate risks. The result of this well-directed management will allow the company to focus on customer satisfaction, providing safe working environments.